Bibliometric and sequence analyses of the pathogenic Helicotylenchus nematodes - Alessio VOVLAS; Ebunoluwa Ijeoma AJOBIEWE; Elena FANELLI; Alberto TROCCOLI; Francesca DE LUCA (Phytopathologia Mediterranea)
Publications between 2000 and 2024 on plant pathogenic species of Helicotylenchus nematodes were reviewed using bibliometric analyses with VOSviewer software. Sequences in GenBank for the same period were used to reconstruct phylogenetic relationships and correctly assign all the Helicotylenchus sequences in the database. The Scopus database was selected for its professional standards, international visibility, broad coverage, and controlled-vocabulary thesaurus available for indexing and retrieving documents. GenBank collects nucleotide sequences and relevant bibliographic and biological annotations for sequence analyses. This study highlighted research trends and specific complexities of working with Helicotylenchus, and the suitability of molecular markers used for identification of the main pathogenic species and confirmation of occurrence of species complexes or cryptic species.